Burundi : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note provides comments and advice on the Poverty Reduction Strategy Paper (PRSP), plans for its implementation, and priorities for strengthening it, including through annual progress reports (APRs) for Burundi. The PRSP highlights that Burundi's weak institutional capacity must be strengthened if the poverty reduction strategy and growth programs are to succeed. There is particular need for improved public financial management and better implementation of socioeconomic policies and reforms over the medium term.